METHODS OF DEVELOPING THE SPORT OF FENCING AND ITS SOLVE - A.T.Saydullayev (Bright Mind Publishing, 2025)
This article discusses the development of fencing and ways to solve problems in this area. Fencing has a positive effect on the physical and mental development of the younger generation, as well as developing skills such as discipline, agility and strategic thinking. Measures that should be implemented in our country in such areas as popularizing fencing, improving infrastructure, training qualified coaches and studying international experience are analyzed. Also, detailed information is provided on the methods of solving them, such as creating conditions for young athletes, organizing competitions and promoting them through the media.
Keywords: Fencing, development, problem solving, physical education, sports infrastructure, training coaches, international experience, competitions, young athletes, sports promotion.